2007
DOI: 10.1017/s1049096507070424
|View full text |Cite
|
Sign up to set email alerts
|

Representations of 9-11 in Editorial Cartoons

Abstract: Throughout American history editorial cartoons have exposed corruption, offered criticism of people in power, questioned and supported policies, and in general given the public another format assisting in the understanding of current events. The freedom to caricature politicians and visually comment on social and political issues has been a hallmark of the editorial cartoonist's profession. In the aftermath of the worldwide furor over Danish cartoonists' use of the Prophet Muhammad's image in early 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“… Diamond’s (2002) analysis aimed at uncovering “themes and motifs” present in cartoons produced in the Muslim and Arab world about 9/11 in its immediate aftermath. Another analysis focused on 9/11 cartoons showed that while some editorial cartoons are edgy and hard-hitting, others seem geared toward simply being funny ( Hoffman & Howard, 2007 ). Bounegru and Forceville’s (2011) study of cartoons about the 2008 global financial crisis is another example of research on editorial cartoons focused on high-profile events.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… Diamond’s (2002) analysis aimed at uncovering “themes and motifs” present in cartoons produced in the Muslim and Arab world about 9/11 in its immediate aftermath. Another analysis focused on 9/11 cartoons showed that while some editorial cartoons are edgy and hard-hitting, others seem geared toward simply being funny ( Hoffman & Howard, 2007 ). Bounegru and Forceville’s (2011) study of cartoons about the 2008 global financial crisis is another example of research on editorial cartoons focused on high-profile events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was also evident to some extent in recent cartoons about North Korea ( Winfield & Yoon, 2002 ). Another analysis found that cartoons published in the immediate aftermath of 9/11 were not terribly critical of the United States and George W. Bush and his administration ( Hoffman & Howard, 2007 ; see also Lamb, 2007 ). So while there are exceptions to this rule, some evidence suggests that editorial cartoons drawn during wartime and other national crises are not terribly critical of government ( Caswell, 2004 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More than just an articulation of existential danger, ‘9/11’ also assigned a particular diagnosis to the attacks: they hate us because of our values , often expressed through the rhetoric of American Exceptionalism (Fierke, 2005; Holland, 2013). Constructing threat to be the result of certain mythologized characteristics of the USA has played a critical explanatory role in how American identity has subsequently been practiced, by both establishing that the attacks were perpetrated for reasons that are deeply embedded in the very character of the USA and by giving the USA and its agents license to (re)act exceptionally (Dittmer, 2005; Dodds, 2008; Hoffman, 2007; Jackson, 2007; Krebs and Lobasz, 2007; Tanguay, 2013).…”
Section: Narrating Insecurity After 9/11mentioning
confidence: 99%
“…The political cartoons are characterized by humor, lack of written information and setting of political agenda (Bormann, Koester, & Bennett, 1978). Next to this, a political cartoon is a format that simplifies the complex political situation and thus helps people to understand current events (Hoffman & Howard, 2007). Newspaper cartoons are a sketch or comic strip, holding a political or social message that generally narrates to present happenings, typically found on the journalistic side of the newsprint.…”
Section: Introductionmentioning
confidence: 99%